Pengaruh Brand Experience, Susceptibility to Normative Influence, Lifestyle, dan Customer Engagement terhadap Brand Loyalty pada Tomoro Coffee - Ardhiansyah Nur Hidayat Idris; Dita Puruwita; Terrylina Arvinta Monoarfa (Indo Publishing, 2026)
The intense competition in Indonesia's modern coffee shop industry requires Tomoro Coffee to build strong brand loyalty. This study aims to analyze the effect of brand experience, susceptibility to normative influence (SNI), lifestyle, and customer engagement on the brand loyalty of Tomoro Coffee consumers in DKI Jakarta. Using a quantitative approach with a causal design, data were collected through an online questionnaire from 150 respondents selected via purposive sampling (criterion: purchase within the last three months). The data were analyzed using multiple linear regression (SPSS 26). The results demonstrate that brand experience, SNI, lifestyle, and customer engagement have a positive and significant effect on brand loyalty, both partially and simultaneously. This model explains 57.9% of the variance in brand loyalty, with customer engagement acting as the most dominant predictor. As a managerial implication, Tomoro Coffee is recommended to strengthen customer engagement through its official application, interactive social media, and customer communities, while maintaining quality consistency relevant to urban lifestyles. Future research is suggested to expand the study area and incorporate variables such as customer satisfaction and brand trust using a longitudinal design.